Loneliness is Associated With Lower Coping Self-Efficacy Among Older Adults. (February 2023) - Lee, Ji W.; Nersesian, Paula V.; Suen, Jonathan J.; Mensah Cudjoe, Thomas K.; Gill, Jessica; Szanton, Sarah L.; Hladek, Melissa D.
To address the gap of lacking research on the association between coping self-efficacy and loneliness, this study examined this relationship to inform future research and intervention on loneliness. Using data from 151 community-dwelling older adults ages 65 and older, we estimated multivariate logistic regression models with age, race/ethnicity, sex, body mass index, chronic disease composite score, social support, coping self-efficacy, and depression symptoms. Loneliness was reported in 32.1% of participants and negatively associated with coping self-efficacy (OR = 0.68, 95% CI: 0.50–0.93) while controlling for age, race, sex, chronic disease composite score, and body mass index. Our findings suggest that coping self-efficacy may be a target for intervention involving loneliness in future research; however, the causal relationship between coping self-efficacy and loneliness should be explored further.